1993
DOI: 10.1177/0032855593073002003
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Career Orientation on Support for Rehabilitation among Correctional Staff

Abstract: Career orientation and work values were examined as factors that may relate to support for rehabilitation among correctional staff. The study surveyed a representative sample of 332 correctional and case management staff from the five geographical regions of the Federal Correctional Service of Canada. Not surprisingly, correctional officers were found to be less supportive of rehabilitation than case management staff. Among correctional officers, possessing favorable attitudes toward the field of corrections, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 19 publications
4
71
0
2
Order By: Relevance
“…The two main correctional staff professional views are support for treatment of inmates and support for punishment of inmates (Robinson, Porporino, & Simourd, 1993). Support for treatment is the degree that an individual supports rehabilitation efforts for inmates (Cullen, Link, Wolfe, & Frank, 1985).…”
Section: Support For Treatment and Support For Punishmentmentioning
confidence: 99%
“…The two main correctional staff professional views are support for treatment of inmates and support for punishment of inmates (Robinson, Porporino, & Simourd, 1993). Support for treatment is the degree that an individual supports rehabilitation efforts for inmates (Cullen, Link, Wolfe, & Frank, 1985).…”
Section: Support For Treatment and Support For Punishmentmentioning
confidence: 99%
“…As a central component of such research, several dimensions have been utilized as both independent and dependent variables. Some of the most studied attitudes are related directly to the correctional occupational environment including, but not limited to, perceptions of dangerousness (e.g., Cullen et al 1985;Triplett et al 1996;Van Voorhis et al 1991), work group cohesion (e.g., Finn 1999;Marston 1993;Paoline et al 2006), instrumental communication (e.g., Lambert et al 2002, job satisfaction (e.g., Byrd et al 2000;Camp 1994;Cullen et al 1989), job stress (e.g., Cullen et al 1985;Grossi et al 1996;, routinization (e.g., Brief et al 1976;Lambert 2004), autonomy (e.g., Lambert 2004;Wright et al 1997), role ambiguity (e.g., Lambert et al 2005;Poole and Regoli 1980;Triplett et al 1996), and job involvement (e.g., Robinson et al 1993Robinson et al , 1996Robinson et al , 1997. What has yet to be part of empirical inquires is the extent to which these attitudes might vary as a function of one's facility assignment (i.e., traditional versus new generation).…”
Section: Occupational Attitudes: Expectations About New Generation Jamentioning
confidence: 99%
“…Farkas (1999) reported that female jail officers were more likely to hold a punitive orientation in comparison to male officers. Likewise, age and tenure have generally not been observed to be associated with views toward inmates (Burton et al 1991;Crouch and Alpert 1982;Cullen et al 1989;Gordon 1999;Leiber 2000;Leiber and Woodrick 1997;Robinson et al 1993), but not always (Farkas 1999;Jurik 1985;Paboojian and Teske 1997).…”
mentioning
confidence: 99%
“…Some research findings suggest that educational level has no relationship with the orientation of correctional staff toward inmates (Crouch and Alpert 1982;Cullen et al 1989;Farkas 1999;Gordon 1999;Jurik 1985;Leiber and Woodrick 1997;Walters 1995), while other studies report that education is positively linked with support for treatment and negatively linked with a punitive custody orientation (Burton et al 1991;Poole and Regoli 1980;Robinson et al 1993;Teske and Williamson 1979). Finally, it has been observed that correctional officers were less supportive of rehabilitation (Robinson et al 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation